Sociomoral atmosphere and prosocial and democratic value orientations in enterprises with different levels of structurally anchored participation - Wolfgang G. Weber; Christine Unterrainer; Thomas Höge (Zeitschrift für Personalforschung (ZfP), 2008)
This study examines effects of structurally anchored organisational democracy on perceived sociomoral atmosphere and on employees' prosocial, democratic behavioural orientations. Data result from the ODEM research project. Beside a description of the concept of sociomoral atmosphere, within this project, 30 small and medium sized enterprises from Austria, North Italy, South Germany, and Liechtenstein (542 participants) were surveyed with questionnaires, interviews, and document analyses. Based on organisational science criteria, several types of enterprises were derived and pooled into three groups of structurally anchored organisational democracy (no, medium, and high democracy). Multivariate group analyses show significant differences between those groups in parts of their prosocial and democratic behavioural orientations and in their sociomoral atmosphere. – – Die vorliegende Arbeit fokussiert die Effekte strukturell verankerter organisationaler Demokratie auf die wahrgenommene soziomoralische Atmosphäre der Beschäftigten und auf deren soziale und demokratieförderliche Handlungsbereitschaften. Vorgestellt werden neben einem Konzeptvorschlag zur soziomoralischen Atmosphäre empirische Ergebnisse aus dem Forschungsprojekt ODEM, in welchem 30 KMUs aus dem deutschsprachigen Raum (542 Probanden) mittels standardisiertem Fragebogen, Experteninterviews und Dokumentenanalysen untersucht wurden. Zur Auswertung wurden - nach organisationswissenschaftlichen Kriterien gebildete - Unternehmenstypen theoriegeleitet zu drei Gruppen struktureller organisationaler Demokratie (keine, mittlere und hohe Demokratieausprägung) zusammengefasst. Multivariate Gruppenvergleiche zeigen signifikante Unterschiede zwischen diesen Gruppen hinsichtlich der soziomoralischen Atmosphäre sowie in Teilen der prosozialen und demokratischen Handlungsbereitschaften.
Keywords: 330; participation; organisational democracy; ethical climate; organisational citizenship behaviour; value orientations; KMU; Mitbestimmung; Mitarbeiterkapitalbeteiligung; Betriebsklima; Mitteleuropa